2004
DOI: 10.1210/jc.2004-0836
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Thyroid Function in Patients Who Received Bone Marrow Transplantation during Childhood and Adolescence

Abstract: An increasing number of long-term surviving bone marrow transplant (BMT) recipients have recovered from their primary disease but are at risk of developing failure of endocrine organs. We investigated 147 patients who underwent allogeneic BMT. Thyroid function was evaluated by serial measurement of basal TSH and free T4 levels as well as by TRH provocative test. Thyroid ultrasound examination was performed for evaluation of thyroid tumor after BMT. Five patients were found to have overt thyroid dysfunction (hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
68
3
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(81 citation statements)
references
References 15 publications
8
68
3
2
Order By: Relevance
“…[24][25][26] The higher rate may be due to treatment at younger age as supported by data from Ishiguro et al 27 and/or due to damage from diagnostic 131 I-MIBG in spite of potassium iodide prophylaxis. 23 While MIBG scans can cause transient hypothyroidism and could have inflated the numbers depending on when thyroid function was checked, permanent thyroid dysfunction is likely a real finding as the rates in the group 10-15 years from treatment were almost double that of the other groups.…”
Section: Discussionmentioning
confidence: 94%
“…[24][25][26] The higher rate may be due to treatment at younger age as supported by data from Ishiguro et al 27 and/or due to damage from diagnostic 131 I-MIBG in spite of potassium iodide prophylaxis. 23 While MIBG scans can cause transient hypothyroidism and could have inflated the numbers depending on when thyroid function was checked, permanent thyroid dysfunction is likely a real finding as the rates in the group 10-15 years from treatment were almost double that of the other groups.…”
Section: Discussionmentioning
confidence: 94%
“…Socie et al 32 reported an incidence of 0.2% of thyroid carcinoma among 3182 children after BMT, with a strong relationship between the occurrence of thyroid cancer and age at BMT. Ishiguro et al 28 reported a high incidence of thyroid adenoma after BMT. However, we found only one case of thyroid tumor (papillary carcinoma) in a patient who underwent BMT at age 14.5 years.…”
Section: Thyroid Dysfunctionmentioning
confidence: 99%
“…This difference may have been due to our previous policy of performing thyroid ultrasound only in patients with palpable thyroid nodules or suspicious consistency of the thyroid gland, and in patients treated with neck or mediastinal irradiation. By contrast, Ishiguro et al 28 performed thyroid ultrasound annually in many of their patients. Our new suggested surveillance approach includes thyroid palpation with performance of thyroid ultrasound in patients with a suspicious consistency of the thyroid gland, or annually in patients after neck, thoraco-mediastinal irradiation or TBI.…”
Section: Thyroid Dysfunctionmentioning
confidence: 99%
See 2 more Smart Citations